The Presence and Absence of Museology Themes in the Educational Process of the Institute of Ethnology and Cultural Anthropology at the University of Warsaw - Katarzyna Waszczyńska (Zbiór Wiadomości do Antropologii Muzealnej, 2023)
The article is devoted to museology education in the Warsaw ethnological centre, from the beginning of its establishment in the 1930s. The text highlights the postulate of the first Head of the Department − Cezaria Baudouin de Courtenay-Ehrenkreutz-Jędrzejewiczowa to combine field research with work with museum collections, the return of museological themes to didactics in the 1960s on the initiative of Marian Pokropek, and the subsequent museological initiatives of the centre’s employees. The conducted review made it possible to conclude that museological issues have always been present in ethnological education in the Warsaw centre, even though it has not been possible to create a uniform system of teaching them. The most popular form of their presence has been the museum traineeship. It brings students into contact with experienced museum professionals, enabling them to acquire specific skills and learn directly about the collections of a particular museum. Students who choose museology subjects do not constitute a large group, but they are interested and committed, which is often reflected in the choice of topics for their diploma theses (bachelor’s, master’s) or in their choice of career after graduation. The article is supplemented by annexes: the first concerns museum traineeships conducted between 2009 and 2022, and the second contains a list of bachelor’s and master’s theses related to museology (it covers the years 1955–2022)